Child Heritage Language Development: An Interplay Between Cross-Linguistic Influence and Language-External Factors - Meir, Natalia; Janssen, Bibi (Frontiers in Psychology, 2021)
The current study investigated the mechanisms of heritage language (HL) development with a focus on case morphology. First, the effects of cross-linguistic influence (i.e., the influence of the properties of the societal language (SL) on the acquisition of the HL) was assessed by performing bilingual vs. monolingual, and between-bilingual group comparisons (Russian–Dutch vs. Russian–Hebrew bilinguals). Russian, Hebrew, and Dutch show differences in the marking of the accusative (ACC) and genitive (GEN) cases, and these differences were used as a basis for the evaluation of cross-linguistic influences. Second, the study evaluated the contribution of language-external factors such as chronological age, age of onset of bilingualism (AoO), languages spoken by the parent to the child (only HL, only SL, both HL and SL), and family language type (both parents are HL speakers, mixed families). Finally, we assessed how language-external factors might potentially mitigate the effects of cross-linguistic influences in bilinguals. Russian-Dutch bilinguals from the Netherlands (n = 39, MAGE = 5.1, SD = 0.8), Russian-Hebrew bilinguals from Israel (n = 36, MAGE = 4.9, SD = 0.9) and monolingual Russian-speaking children (n = 41, MAGE = 4.8, SD = 0.8), along with adult controls residing in the Russian Federation, participated in the study. The case production of ACC and GEN cases was evaluated using elicitation tasks. For the bilinguals, the background data on individual language-external factors were elicited from the participants. The results show that case morphology is challenging under HL acquisition—case acquisition in the HL is impeded under the influence of the properties of the SL. This is evident in the lower performance of both bilingual groups, compared with the monolingual controls who showed ceiling performance in the production of target inflection in the ACC and GEN contexts. More specifically, the acquisition of morphology is hindered when there are differences in the mapping of functional features (such as with Russian-Hebrew bilinguals) and/or the absence of this feature marking (such as with Russian-Dutch bilinguals). But the findings also point to the involvement of language-external factors as important mitigators of potential negative effects of cross-linguistic influence. In summary, HL development is an intricate interplay between cross-linguistic influence and language-external factors.